Determination of Antimicrobial Susceptibility Patterns between Different Strains of Propionibacterium Acnes - N., Yusufu, W.; O., Suleiman, H.; Y., Akwa, V.; L., David, D.; A., Taiga, (International Journal of Innovative Research in Medical Science, 2019)
Propionibacterium acnes (P. acnes) isolated in infections of deep tissues was originally thought to be as a result of improper sterilization of skin and hence contamination of medical processes with this commensal/ normal flora of the skin. P. acnes has latter been identified as the principal agent responsible for the progression of some deep tissue diseases. The antimicrobial susceptibility patterns between different strains of P. acnes was determined. Ten (10) P. acnes clinical isolates of infections were considered, two (2) from acne vulgaris and eight (8) [two (2) per recA types 1A1, 1B, II and III] from lumber herniation tissues. Antibiotic susceptibility of some antibiotics was also determined and resistance to tetracycline was seen in 1 isolate, trimethoprim (1 isolate) and weak activity seen in 5 isolates. Heteroresistance to rifampicin was witnessed among 6 isolates. Upon four days of incubation, no inhibition of the bacterial growth by tetracycline in isolate 1(III). Isolate 17(1B) had no inhibition from trimethoprim. There was low inhibition of P. acnes by this antibiotic in isolates 71(IA1), 82(IB), 55(II), 1 (III) and 64(III). Amoxicillin and rifampicin created greater zones of inhibition among P. acnes isolates. Erythromycin was the next most inhibiting antibiotic with greater inhibition zones. Although Rifampicin had large inhibition zones, heteroresistance was observed among isolates 82(IB), 24(II), I (III), 17(IB), 55(II) and 71(IA1) as colonies were observed growing within the zones after 4 days of incubation. The antibiotics resistance expressed in the study were seen displayed among the lumber disc herniation isolates only with none involving acne vulgaris isolates. This study supports the theory that most P. acnes isolates in deep tissues exhibit higher rate of antibiotic resistance. P. acnes hence might be named the etiological agent of foreign-body infections like infections of indwelling medical devices.